Gas sensor for detecting dimethyl trisulfide as well as preparation method and application of gas sensor
By using Cu-doped Co3O4 porous nanorod material as a sensitive body, its structure is optimized to increase catalytic active sites, the problem of difficult to detect low-active sulfide substances in the prior art is solved, and efficient detection of dimethyl trisulfide is achieved.
Patent Information
- Application Number
- CN202411969071.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Existing metal oxide gas sensors are difficult to achieve high selectivity and high sensitivity when detecting low-active sulfide materials, especially in the presence of mixed gases or interfering gases.
Cu-doped Co3O4 porous nanorod material is used as a sensitive body. By optimizing its micromorphology and porous structure, more catalytic oxidation active sites on the surface are constructed, and specific adsorption and catalytic oxidation reactions of dimethyl trisulfide molecules are promoted on the surface of the material.
High selectivity and high sensitivity detection of dimethyl trisulfide is achieved, the target gas can be accurately identified under complex and multiple gas conditions, and the actual concentration sensitivity of the detection is improved to 10 ppb.
Smart Images

Figure HDA0005219087010000011 
Figure HDA0005219087010000012 
Figure HDA0005219087010000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gas sensors, and in particular relates to a gas sensor for detecting dimethyl trisulfide and a preparation method thereof. Background Art
[0002] The flavor of edible vegetable oils is an important product attribute and characteristic mark. The characteristic flavor components are mainly aldehydes, alcohols, pyrazine compounds, sulfides, etc. After studying the formation pathways and mechanisms of different flavor substances in vegetable oils, it was found that sulfides have a low odor threshold and are an important class of key flavor compounds. Their content can best reflect the characteristics and quality changes of oil products. At present, this type of flavor substance is mainly detected by analytical equipment such as gas chromatography-mass spectrometry. However, due to the low chemical activity of these sulfides (such as dimethyl trisulfide), it is challenging to detect them with high sensitivity.
[0003] Gas sensors based on semiconductor metal oxides have been widely used in various fields such as industry, environmental monitoring, and food testing due to their advantages such as small size, low energy consumption, and good stability. However, due to the limitations of the gas-sensing mechanism, most metal oxide gas sensors usually respond to multiple gases. When detecting mixed gases or in the presence of interfering gases, it is difficult to effectively identify and detect the target components, especially for low-activity sulfide substances. Summary of the invention
[0004] The main purpose of the present invention is to provide a highly selective and highly sensitive gas sensor for detecting dimethyl trisulfide in view of the problems and shortcomings of the prior art.
[0005] Another object of the present invention is to provide a method for preparing and applying the above-mentioned dimethyl trisulfide gas sensor, which involves relatively simple preparation steps, is easy to operate, and is suitable for popularization and application.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A gas sensor for detecting dimethyl trisulfide, wherein the dimethyl trisulfide gas sensor uses a Cu-doped Co3O4 porous nanorod material as a sensitive body; the pore size of the Cu-doped Co3O4 porous nanorod material is 2-50 nm; the length is 2-10 μm, and the diameter is 0.5-2 μm; the gas sensor uses the surface porous Cu-doped Co3O4 material as a sensitive body, and by optimizing its microscopic morphology and porous structure, more catalytic oxidation active sites on the surface are constructed, and low-activity dimethyl trisulfide molecules are promoted to undergo specific adsorption and catalytic oxidation reactions on the surface of the porous Cu-doped Co3O4 material, thereby effectively ensuring specific detection of dimethyl trisulfide molecules and improving their detection sensitivity.
[0008] In the above scheme, the gas sensor for detecting methyl trisulfide comprises several sensitive layers composed of Cu-doped Co3O4 porous nanorod materials.
[0009] Furthermore, the sensitive layer is formed by coating a Cu-doped Co3O4 porous nanorod material dispersion onto the electrode surface and then drying it.
[0010] Furthermore, the gas sensor for detecting methyl trisulfide contains 2 to 7 sensitive layers.
[0011] Optionally, the resistance of the dimethyl trisulfide gas sensor is 100-1000 KΩ.
[0012] Optionally, the resistance value of the dimethyl trisulfide gas detection gas sensor is selected from any value of 100KΩ, 200KΩ, 300KΩ, 500KΩ, 600KΩ, 800KΩ, 1000KΩ or a range between any two of the above values.
[0013] In the above scheme, the Cu-doped Co3O4 porous nanorod material is prepared by solvent thermal reaction and annealing using cobalt salt, copper salt, organic ligand and solvent as main raw materials; the specific preparation steps are as follows:
[0014] 1) dispersing cobalt salt, copper salt and organic ligand in a solvent to obtain a uniform dispersion;
[0015] 2) subjecting the obtained dispersion to a solvothermal reaction, followed by washing and drying;
[0016] 3) Annealing the obtained dried product in air to obtain Cu-doped Co3O4 porous nanorod material.
[0017] Optionally, the cobalt salt is selected from at least one of cobalt nitrate, cobalt acetate and the like.
[0018] Optionally, the copper salt is selected from copper nitrate, copper chloride and the like.
[0019] Optionally, the organic ligand may be 2-methylimidazole or the like.
[0020] Optionally, the molar ratio of the cobalt salt to the organic ligand is 1:1-32.
[0021] Furthermore, the molar ratio of the cobalt salt to the organic ligand is selected from any value of 1:1, 1:2, 1:4, 1:8, 1:16, 1:32 or a range between any two of the above values.
[0022] Optionally, the molar ratio of the copper salt to the cobalt salt is 1:20-100.
[0023] Furthermore, the molar ratio of the copper salt to the cobalt salt is selected from any value of 1:20, 1:40, 1:60, 1:80, 1:100 or a range between any two of the above values.
[0024] Optionally, the solvent is selected from one or more of water, ethanol, methanol and the like.
[0025] Optionally, the ratio of the cobalt salt to the solvent is 0.1-2.5 mol: 3-60 mL.
[0026] Optionally, the temperature of the solvent thermal reaction is 60 to 180° C., and the time is 12 to 20 hours.
[0027] Optionally, the annealing temperature is 300-600° C., and the annealing time is 2-6 hours.
[0028] Furthermore, the heating system adopted in the annealing step includes: first heating to 150-200°C at a rate of 2-5°C / min and keeping warm for 1-2h; then heating to 300-600°C at a rate of 1-3°C / min and keeping warm for 2-6h.
[0029] The present invention also provides a method for preparing a dimethyl trisulfide gas detection gas sensor, comprising the following steps:
[0030] The Cu-doped Co3O4 porous nanorod material dispersion is coated on the electrode surface and dried naturally at room temperature to obtain the dimethyl trisulfide detection gas sensor.
[0031] Optionally, the coating may be performed by drip coating or other methods.
[0032] Optionally, the solvent used in the Cu-doped Co3O4 porous nanorod material dispersion is selected from at least one of ethanol, methanol, acetone, acetonitrile, toluene, and n-hexane; the mass volume ratio of the Cu-doped Co3O4 porous nanorod material to the solvent is 2-20 mg: 0.5-20 mL.
[0033] Optionally, for the electrode surface per unit area, the amount of Cu-doped Co3O4 porous nanorod material dispersion droplet coating is 0.002-0.006 mL / cm 2 .
[0034] Optionally, the number of dripping is 2 to 8 times.
[0035] Optionally, the room temperature natural drying conditions are 15-30° C. and 10-90% RH.
[0036] The present invention also provides an application method of the above-mentioned gas sensor for detecting dimethyl trisulfide, wherein the working temperature is 100-200° C.; the concentration of dimethyl trisulfide that can be detected is as low as 1-100 ppm.
[0037] Furthermore, the gas sensor for detecting dimethyl trisulfide shows high selectivity for dimethyl trisulfide under complex multi-gas conditions, and other gases include alcohols, aldehydes, etc.
[0038] The dimethyl trisulfide gas detection gas sensor of the present invention uses cobalt salt, copper salt and organic ligand as main raw materials, and synthesizes Co3O4 nanorod material with porous surface and Cu doped through hydrothermal and annealing, and uses it as a sensitive body, and achieves the purpose of improving the high selectivity and sensitivity of detection by enhancing the interaction of dimethyl trisulfide molecules on its surface. The Cu doped Co3O4 porous nanorod material is deposited on the electrode surface through a solution coating process to prepare a gas sensor for the detection of the flavor substance dimethyl trisulfide; the obtained sensor has a good response to dimethyl trisulfide gas, and the actual concentration that can be detected is as low as 10ppb. In addition, it shows a certain selectivity under the condition of the presence of other organic gases. The sensor can be used as an effective tool for detecting the flavor of samples such as vegetable oil and judging the quality of samples such as edible vegetable oil.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1) The present invention uses Cu-doped porous Co3O4 material as a sensitive body to enhance the specific interaction of dimethyl trisulfide molecules on its surface, which can effectively ensure the selectivity of the sensitive element.
[0041] 2) The present invention achieves high-sensitivity detection of dimethyl trisulfide gas by the obtained composite material through means such as surface pore size structure optimization and Cu doping Co3O4.
[0042] 3) The preparation method and application method of the sensor of the present invention are simple and reliable, easy to operate, and have good practicality. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a transmission electron microscope image of the porous Cu-doped Co3O4 nanomaterial obtained in Example 1;
[0044] Figure 2 N2 adsorption-desorption curve and pore size distribution of Cu-doped Co3O4 nanomaterials obtained in Example 1;
[0045] Figure 3 The response effect of the two-layer sensitive film sensor obtained in Example 1 to 10 ppb dimethyl trisulfide gas;
[0046] Figure 4 The scanning electron microscope image and XRD structure image of the porous Cu-doped Co3O4 nanomaterial obtained in Example 2;
[0047] Figure 5 N2 adsorption-desorption curve and pore size distribution of the porous Cu-doped Co3O4 material in Example 2;
[0048] Figure 6 This is the response effect of the 5-layer sensitive film sensor obtained in Example 2 to 20 ppb dimethyl trisulfide gas. DETAILED DESCRIPTION
[0049] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples. These descriptions are only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention.
[0050] In the following examples, unless otherwise specified, the raw materials used were purchased from commercial sources.
[0051] In the following embodiments, the gas sensor uses porous Cu-doped Co3O4 nanorod material as a sensitive material to achieve high-sensitivity detection of low-concentration dimethyl trisulfide gas; the preparation steps of the porous Cu-doped Co3O4 material are as follows:
[0052] 1) Cobalt salt, copper salt and 2-methylimidazole are uniformly dispersed in 40 mL of deionized water in a molar ratio of 1:0.02:1-32;
[0053] 2) Transfer the entire solution into a 50 mL polytetrafluoroethylene-lined autoclave and keep it at 60-180°C for 12 hours;
[0054] 3) The precipitate was collected by centrifugation and washed with deionized water several times. Finally, it was dried at 60°C overnight and annealed at 300-600°C in air atmosphere for 2 hours to obtain the porous Co3O4 nanorods.
[0055] A single sensor is prepared by spin coating, and the specific steps are as follows:
[0056] 1) 2-20 mg of porous Cu-doped Co3O4 material is uniformly dispersed in 0.5-20 mL of solvent (one or more mixtures of ethanol, methanol, acetone, acetonitrile, toluene, and n-hexane);
[0057] 2) Take a certain volume of the dispersed porous Cu-doped Co3O4 material described in step 1), drop it on the surface of 2 to 8 planar interdigitated electrodes, and place it at room temperature to fully dry, so as to construct a porous Cu-doped Co3O4 sensitive membrane; the dispersion liquid is dropped on the surface of different ceramic tube interdigitated electrodes for different times to obtain multiple sensitive membranes with different thicknesses and surface densities; thus, the gas sensor is obtained.
[0058] The gas sensor operates at 100-200° C., and has a resistance value of 100-1000 KΩ in the air.
[0059] Example 1
[0060] A gas sensor for detecting dimethyl trisulfide, the preparation method of which comprises the following steps:
[0061] 1) Disperse 2.5 mmol of cobalt nitrate hexahydrate, 0.05 mmol of copper nitrate trihydrate, and 40 mmol of 2-methylimidazole in 40 mL of deionized water and mix well under magnetic stirring;
[0062] 2) Transfer the entire solution into a 50 mL polytetrafluoroethylene-lined autoclave and keep it at 120 °C for 12 h;
[0063] 3) collecting the precipitate by centrifugation and washing with deionized water several times; drying at 60°C overnight, heating to 200°C at a rate of 5°C / min in an air atmosphere, keeping the temperature for 2h, and then heating to 500°C at a rate of 3°C / min and keeping the temperature for 2h to obtain Cu-doped Co3O4 porous nanorod material;
[0064] 4) Ultrasonically disperse 5 mg of the prepared Cu-doped Co3O4 porous nanorod material in 5 mL of ethanol to obtain a nanorod dispersion;
[0065] 5) Take 5 μL of the obtained nanorod dispersion and drip 1, 2, ..., 5 times of 5 μL of the dispersion on 5 ceramic tube interdigital electrodes (the ceramic tube has a length of 4 mm, an outer diameter of 1.2 mm, a wall thickness of 0.2 mm, and two pairs of gold interdigital electrode channels are 2 mm) respectively, to obtain 5 sensors with 1, 2, ..., 5 layers of sensitive membranes respectively; the preparation steps of the single-layer sensitive membrane are as follows: drop the porous Co3O4 nanorod dispersion on the surface of a ceramic tube interdigital electrode, and place it at room temperature 25°C to dry naturally for 6 hours until the organic solvent is completely evaporated to construct a layer of sensitive membrane.
[0066] Figure 1 This is a transmission electron microscope image of the Cu-doped Co3O4 porous nanomaterial obtained in this example. It can be seen that the obtained material presents a nanorod-like structure with a length of about 5 to 7 μm. The average diameter of a single nanorod is about 1 μm, and it has a porous structure. Figure 2 The pore size distribution in the sample further proves that its surface pore size is 2 to 50 nm, and its surface pore size is concentrated at 30.1 nm.
[0067] The resistance value of the sensors with different numbers of sensitive film layers obtained in this embodiment under the heating condition of 150°C is between 100 and 1000 KΩ. The response value of the sensor is defined as S = R g / R a , where R a , R g are the resistance values of the sensor in air and in the gas to be measured, respectively.
[0068] The five gas sensors prepared in this example were used to test the sensitivity and response performance of dimethyl trisulfide. The operating temperature of the sensors was 150°C. The results showed that when the porous Cu-doped Co3O4 sensitive body was spin-coated twice, the response value to dimethyl trisulfide was the highest. Figure 3 As shown, the sensor with optimized film thickness (spin coated twice) can achieve a significant response to 10ppb dimethyl trisulfide gas; it can achieve preliminary identification of the flavor and quality of samples such as edible vegetable oils.
[0069] Further tests show that the gas sensor for detecting dimethyl trisulfide obtained in this embodiment still exhibits high selectivity for dimethyl trisulfide under conditions involving complex multiple gases (including formaldehyde, methanol, ethanol, etc.).
[0070] Example 2
[0071] A gas sensor for detecting dimethyl trisulfide, the preparation method of which comprises the following steps:
[0072] 1) Disperse 2 mmol of cobalt nitrate hexahydrate, 0.02 mmol of copper nitrate trihydrate, and 60 mmol of 2-methylimidazole in 40 mL of methanol and mix well under magnetic stirring;
[0073] 2) Transfer the entire solution into a 50 mL polytetrafluoroethylene-lined autoclave and keep it at 80 °C for 12 h;
[0074] 3) collecting the precipitate by centrifugation and washing with methanol several times; drying at 60°C overnight, first heating to 150°C at a rate of 5°C / min in an air atmosphere, keeping the temperature for 2 hours, and then heating to 300°C at a rate of 1°C / min and keeping the temperature for 2 hours to obtain a Cu-doped Co3O4 porous nanorod material;
[0075] 4) 2 mg of the prepared Cu-doped Co3O4 porous nanorod material was uniformly dispersed in 10 mL of ethanol by ultrasound to obtain a nanorod dispersion;
[0076] 5) Take 5 μL of the obtained nanorod dispersion and drip 1, 2, ..., 5 times of 5 μL of the dispersion on 5 ceramic tube interdigital electrodes (the ceramic tube has a length of 4 mm, an outer diameter of 1.2 mm, a wall thickness of 0.2 mm, and two pairs of gold interdigital electrode channels are 2 mm) respectively, to obtain 5 sensors with 1, 2, ..., 5 layers of sensitive film thickness respectively; the preparation steps of the single-layer sensitive film are as follows: drop the porous Co3O4 nanorod dispersion on the surface of a ceramic tube interdigital electrode, and place it at room temperature 25°C to dry naturally for 6 hours until the organic solvent is completely evaporated to construct a layer of sensitive film.
[0077] Figure 4 This is a scanning electron microscope image of the Cu-doped Co3O4 porous nanomaterial obtained in this example. It can be seen that the obtained material presents a nanorod-like structure with a length of about 0.5 to 3 μm, a single nanorod diameter of 200 to 500 nm, and a surface pore size of 5 to 50 nm. Figure 5 The N2 adsorption-desorption experiment further confirmed that its surface pore size is concentrated at 12nm.
[0078] The sensor obtained in this embodiment has a resistance value of 100 to 1000 KΩ under the heating condition of 180°C. The response value of the sensor is defined as S = R g / R a , where R a , R g are the resistance values of the sensor in air and in the gas to be measured, respectively.
[0079] The five gas sensors prepared in this example were used to test the sensitivity and response performance of dimethyl trisulfide. The operating temperature of the sensors was 180°C. The results showed that when the porous Cu-doped Co3O4 sensitive body was spin-coated five times, the response value to dimethyl trisulfide was the highest. Figure 6 As shown, the sensor after optimizing the film thickness (spin coating 5 times) can achieve a significant response to 20ppb dimethyl trisulfide gas, which can realize the preliminary identification of oil flavor and quality.
[0080] Further tests show that the gas sensor for detecting dimethyl trisulfide obtained in this embodiment still exhibits high selectivity for dimethyl trisulfide under conditions involving complex multiple gases (including formaldehyde, methanol, ethanol, etc.).
[0081] Comparative Example 1
[0082] A gas sensor for detecting dimethyl trisulfide, the preparation method of which is substantially the same as that of Example 1, except that: the corresponding copper salt (copper nitrate trihydrate) is not introduced during the preparation process.
[0083] The results show that the obtained sensor has almost no response to the target gas (dimethyl trisulfide).
[0084] Comparative Example 2
[0085] A gas sensor for detecting dimethyl trisulfide, the preparation method of which is substantially the same as that of Example 1, except that: Step 3) the annealing step is: directly heating to 500°C at a rate of 5°C / min in an air atmosphere and keeping the temperature for 2h to obtain porous Co3O4 nanorods.
[0086] The results showed that the obtained sensor had no response to dimethyl trisulfide.
[0087] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.
Claims
1. A gas sensor for detecting dimethyl trisulfide, characterized in that: The dimethyl trisulfide gas sensor uses Cu-doped Co3O4 porous nanorod material as a sensitive body; the pore size of the Cu-doped Co3O4 porous nanorod material is 2-50nm; the length is 2-10μm, and the diameter is 0.5-2μm.
2. The gas sensor according to claim 1, characterized in that The gas sensor for detecting methyl trisulfide comprises several sensitive layers composed of Cu-doped Co3O4 porous nanorod materials.
3. The gas sensor according to claim 1, characterized in that: The Cu-doped Co3O4 porous nanorod material is prepared by using cobalt salt, copper salt, organic ligand and solvent as main raw materials and undergoing solvent thermal reaction and annealing.
4. The gas sensor according to claim 3, characterized in that: The cobalt salt is at least one of cobalt nitrate and cobalt acetate; the copper salt is one of copper nitrate and copper chloride; and the organic ligand is 2-methylimidazole.
5. The gas sensor according to claim 3, characterized in that: The molar ratio of the cobalt salt to the organic ligand is 1:1-32; the molar ratio of the copper salt to the cobalt salt is 1:20-100.
6. The gas sensor according to claim 3, characterized in that: The temperature of the solvent thermal reaction is 60-180° C., and the time is 12-20 hours; the temperature of the annealing is 300-600° C., and the time is 2-6 hours.
7. The gas sensor according to claim 3, characterized in that: The temperature rise system adopted in the annealing step includes: firstly heating to 150-200°C at a rate of 2-5°C / min and keeping the temperature for 1-2h; then heating to 300-600°C at a rate of 1-3°C / min.
8. The method for preparing the gas sensor for detecting dimethyl trisulfide according to claim 1, characterized in that: The method comprises the following steps: coating a dispersion of Cu-doped Co3O4 porous nanorod material onto an electrode surface, and drying at room temperature to obtain the gas sensor for detecting dimethyl trisulfide.
9. The preparation method according to claim 8, characterized in that: The solvent used in the dispersion of the Cu-doped Co3O4 porous nanorod material is at least one of ethanol, methanol, acetone, acetonitrile, toluene and n-hexane; the mass volume ratio of the Cu-doped Co3O4 porous nanorod material to the solvent is 2-20 mg: 0.5-5 mL.
10. A method for using the gas sensor for detecting dimethyl trisulfide according to any one of claims 1 to 7 or the gas sensor for detecting dimethyl trisulfide obtained by the preparation method according to any one of claims 8 to 9, characterized in that: The working temperature is 100-200°C; the concentration of dimethyl trisulfide detected is as low as 1-100 ppm.
Citation Information
Patent Citations
Functionalized nanotube sensors and related methods
CA2889843A1
Cobaltosic oxide nano sheet hollow ball and preparation method and applications thereof
CN107356639A
CuO and Co3O4 heterostructure nanowire composite sensitive material, ethylene glycol sensor and preparation methods
CN110514700A
High-sensitivity electrochemical sensor for detecting nitrite, preparation method thereof and application thereof
CN110672684A
Low-detection-limit dimethyl trisulfide gas-sensitive sensor material as well as preparation method and application thereof
CN115420775A